MADS-box Transcription Factor OsMADS25 Regulates Root Development through Affection of Nitrate Accumulation in Rice - Yu, Chunyan (PLoS One, 2015)
MADS-box transcription factors are vital regulators participating in plant growth and development process and the functions of most of them are still unknown. ANR1 was reported to play a key role in controlling lateral root development through nitrate signal in Arabidopsis. OsMADS25 is one of five ANR1-like genes in Oryza Sativa and belongs to the ANR1 clade. Here we have investigated the role of OsMADS25 in the plant’s responses to external nitrate in Oryza Sativa. Our results showed that OsMADS25 protein was found in the nucleus as well as in the cytoplasm. Over-expression of OsMADS25 significantly promoted lateral and primary root growth as well as shoot growth in a nitrate-dependent manner in Arabidopsis. OsMADS25 overexpression in transgenic rice resulted in significantly increased primary root length, lateral root number, lateral root length and shoot fresh weight in the presence of nitrate. Down-regulation of OsMADS25 in transgenic rice exhibited significantly reduced shoot and root growth in the presence of nitrate. Furthermore, over-expression of OsMADS25 in transgenic rice promoted nitrate accumulation and significantly increased the expressions of nitrate transporter genes at high rates of nitrate supply while down-regulation of OsMADS25 produced the opposite effect. Taken together, our findings suggest that OsMADS25 is a positive regulator control lateral and primary root development in rice.